ChemInform Abstract: Organocatalytic Enantioselective Construction of Multi‐Functionalized Spiro Oxindole Dienes. Issue 48 (2nd December 2014) - Huang, Xiao‐Fei; Zhang, Ya‐Fei; Qi, Zheng‐Hang; Li, Nai‐Kai; Geng, Zhi‐Cong; Li, Kun; Wang, Xing‐Wang
Abstract A diastereo‐ and enantioselective domino Michael‐cyclization‐tautomerization reaction of isatylidene malononitriles (I) and (IV) with α, α‐dicyanoalkenes catalyzed by a chinchona alkaloid‐derived bifunctional catalyst is reported.